Extracellular vesicles from a novel Lactiplantibacillus plantarum strain suppress inflammation and promote M2 macrophage polarization - Gong, Shuang; Zeng, Ruixia; Liu, Ling; Wang, Rui; Xue, Man; Dong, Hao; Wu, Zhigang; Zhang, Yibo (Frontiers in Immunology, 2024)
Background Lactiplantibacillus plantarum (L. plantarum) is known for its probiotic properties, including antioxidant and anti-inflammatory effects. Recent studies have highlighted the role of extracellular vesicles (EVs) from prokaryotic cells in anti-inflammatory effects. Objective This study aims to investigate the anti-inflammatory effects of extracellular vesicles derived from a newly isolated strain of L. plantarum (LP25 strain) and their role in macrophage polarization. Methods The LP25 strain and its extracellular vesicles were isolated and identified through genomic sequencing, transmission electron microscopy (TEM), and nanoparticle tracking analysis (NTA). RAW 264.7 cells were treated with lipopolysaccharide (LPS) and/or LP25-derived extracellular vesicles (LEV). Morphological changes in the cells were observed, and the expression levels of pro-inflammatory cytokines (TNF-α, IL-6)、iNOS and anti-inflammatory cytokines (IL-10) 、Arg-1 were measured using quantitative real-time PCR (qPCR). Flow cytometry was used to detect the expression of Arg-1 in the treated cells. Results Treatment with LP25 EVs led to significant morphological changes in RAW 264.7 cells exposed to LPS. LP25 EVs treatment resulted in increased expression of Arg-1 and anti-inflammatory cytokines IL-10, and decreased expression of iNOS and surface markers protein CD86. Flow cytometry confirmed the increased expression of the M2 macrophage marker Arg-1 in the LP25 EVs-treated group. Conclusion Extracellular vesicles from Lactiplantibacillus plantarum LP25 can suppress inflammatory responses and promote the polarization of macrophages toward the anti-inflammatory M2 phenotype. These findings provide new evidence supporting the anti-inflammatory activity of L. plantarum-derived EVs.